The effect of medium-chain triacylglycerols on the blood lipid profile of male endurance runners - Kern, M.; Lagomarcino, N. D.; Misell, L. M.; Schuster, V. V. (2000)
Medium-chain triacylglycerol (MCT) oil is currently marketed for athletes as an ergogenic aid for optimal performance. Research assessing the blood lipid response of humans to MCT consumption is very limited and inconclusive. In this randomized cross-over study, male endurance runners (aged 30.5 +/- 5.5 years) were instructed to consume a low-fat diet (approximately 15% of energy) and consume either supplemental MCT oil (30 g twice each day) or long-chain triacylglycerol (LCT) oil (28 g corn oil twice each day) for 14 days. Each dietary trial was separated by at least 3 weeks. At the end of each trial, fasting blood samples were collected and analyzed for serum concentrations of total cholesterol (TC), high density lipoprotein-cholesterol (HDL-C), low density lipoprotein-cholesterol (LDL-C), and triacylglycerol (TG). Concentrations of TC (3.83 +/- 0.12 vs. 3.41 +/- 0.15 mmol/L, P = 0.004), LDL-C (1.76 +/- 0.12 vs. 1.51 +/- 0.14 mmol/L, P = 0.033), and TG (1.26 +/- 0.14 vs. 0.98 +/- 0.12 mmol/L, P = 0.006) were higher following the MCT trial than following the LCT trial, respectively. HDL-C concentration did not differ significantly between trials (MCT 1.48 +/- 0.05 mmol/L vs. LCT 1.45 +/- 0.04 mmol/L, P = 0.465). Although blood lipids remained within desirable ranges established by the National Cholesterol Education Program, these results suggest that consumption of MCT oil for 2 weeks negatively alters the blood lipid profile of athletes. Future studies should determine the effects of longer periods of MCT supplementation on serum lipids of exercisers and other groups of individuals. With little data suggesting that MCT are ergogenic, the adverse effects of MCT on blood lipid concentrations may outweigh any proposed benefits for athletes. Medium-chain triacylglycerol (MCT) oil is currently marketed for athletes as an ergogenic aid for optimal performance. Research assessing the blood lipid response of humans to MCT consumption is very limited and inconclusive. In this randomized cross-over study, male endurance runners (aged 30.5 +/- 5.5 years) were instructed to consume a low-fat diet (approximately 15% of energy) and consume either supplemental MCT oil (30 g twice each day) or long-chain triacylglycerol (LCT) oil (28 g corn oil twice each day) for 14 days. Each dietary trial was separated by at least 3 weeks. At the end of each trial, fasting blood samples were collected and analyzed for serum concentrations of total cholesterol (TC), high density lipoprotein-cholesterol (HDL-C), low density lipoprotein-cholesterol (LDL-C), and triacylglycerol (TG). Concentrations of TC (3.83 +/- 0.12 vs. 3.41 +/- 0.15 mmol/L, P = 0.004), LDL-C (1.76 +/- 0.12 vs. 1.51 +/- 0.14 mmol/L, P = 0.033), and TG (1.26 +/- 0.14 vs. 0.98 +/- 0.12 mmol/L, P = 0.006) were higher following the MCT trial than following the LCT trial, respectively. HDL-C concentration did not differ significantly between trials (MCT 1.48 +/- 0.05 mmol/L vs. LCT 1.45 +/- 0.04 mmol/L, P = 0.465). Although blood lipids remained within desirable ranges established by the National Cholesterol Education Program, these results suggest that consumption of MCT oil for 2 weeks negatively alters the blood lipid profile of athletes. Future studies should determine the effects of longer periods of MCT supplementation on serum lipids of exercisers and other groups of individuals. With little data suggesting that MCT are ergogenic, the adverse effects of MCT on blood lipid concentrations may outweigh any proposed benefits for athletes. Medium-chain triacylglycerol (MCT) oil is currently marketed for athletes as an ergogenic aid for optimal performance. Research assessing the blood lipid response of humans to MCT consumption is very limited and inconclusive. In this randomized cross-over study, male endurance runners (aged 30.5 +/- 5.5 years) were instructed to consume a low-fat diet (approximately 15% of energy) and consume either supplemental MCT oil (30 g twice each day) or long-chain triacylglycerol (LCT) oil (28 g corn oil twice each day) for 14 days. Each dietary trial was separated by at least 3 weeks. At the end of each trial, fasting blood samples were collected and analyzed for serum concentrations of total cholesterol (TC), high density lipoprotein-cholesterol (HDL-C), low density lipoprotein-cholesterol (LDL-C), and triacylglycerol (TG). Concentrations of TC (3.83 +/- 0.12 vs. 3.41 +/- 0.15 mmol/L, P = 0.004), LDL-C (1.76 +/- 0.12 vs. 1.51 +/- 0.14 mmol/L, P = 0.033), and TG (1.26 +/- 0.14 vs. 0.98 +/- 0.12 mmol/L, P = 0.006) were higher following the MCT trial than following the LCT trial, respectively. HDL-C concentration did not differ significantly between trials (MCT 1.48 +/- 0.05 mmol/L vs. LCT 1.45 +/- 0.04 mmol/L, P = 0.465). Although blood lipids remained within desirable ranges established by the National Cholesterol Education Program, these results suggest that consumption of MCT oil for 2 weeks negatively alters the blood lipid profile of athletes. Future studies should determine the effects of longer periods of MCT supplementation on serum lipids of exercisers and other groups of individuals. With little data suggesting that MCT are ergogenic, the adverse effects of MCT on blood lipid concentrations may outweigh any proposed benefits for athletes. J. Nutr. Biochem. 2000 May 1;11(5):288-292